Positive electrode for all-solid-state rechargeable battery and all-solid-state rechargeable battery including same
By introducing cyclic disulfonamide anionic soft viscous crystals into the positive electrode of an all-solid-state rechargeable lithium battery, the problem of battery performance degradation caused by volume changes during charging and discharging is solved, and the battery stability and energy density are improved under low constraint pressure.
Patent Information
- Application Number
- CN202480031513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-12
- Filing Date
- 2024-03-13
- Publication Date
- 2025-12-05
AI Technical Summary
In all-solid-state rechargeable lithium batteries, volume changes in the positive electrode active material lead to loss of contact with adjacent solid electrolytes or conductive additives, resulting in a decline in battery performance. Existing technologies use pressurized clamps, which increases costs and reduces energy density.
A positive electrode mixture layer containing soft, viscous crystals of cyclic disulfonamide anions (such as 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonamide anion) is used to suppress volume changes during charging and discharging and reduce dependence on external pressure.
Even under conditions of no external pressure or low constraint pressure, it effectively suppresses the degradation of battery performance and improves battery stability and energy density.
Smart Images

Figure CN121079787A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a positive electrode for a full solid rechargeable battery and a full solid rechargeable battery including the positive electrode. BACKGROUND
[0002] In a full solid rechargeable lithium battery, it is known that the volume of the positive electrode active material changes depending on charging and discharging due to lithium intercalation or deintercalation into the positive electrode active material during charging.
[0003] With an increase in the volume change, there is a risk that the positive electrode active material can lose contact with the adjacent solid electrolyte or conductive aid, resulting in a decrease in battery performance.
[0004] Accordingly, in order to suppress the influence of the volume change of the active material during charging and discharging, conventionally, a full solid lithium ion rechargeable battery is inserted from the thickness direction using an end plate or the like, and charging and discharging are performed in a state in which a high external pressure is applied therein.
[0005] However, the presence of a pressurizing jig for applying a high external pressure to the full solid rechargeable battery is not only disadvantageous in terms of cost, but also becomes a factor that reduces the energy density of the entire battery module including the full solid rechargeable battery and the pressurizing jig. PRIOR ART
[0006] [Patent Document 1] Japanese Laid-Open Publication No. 2021-131979
[0007] [Patent Document 2] Japanese Laid-Open Publication No. 2020-198270 SUMMARY
[0008]
Technical Problem
[0009] The present invention was made in view of the foregoing problems, and aims to provide a full solid rechargeable battery capable of suppressing deterioration of battery performance even when charging and discharging are performed at a low restraint pressure that can be achieved without applying an external pressure or using a simple jig. The low restraint pressure can be, for example, a restraint pressure of less than or equal to 0.5 MPa.
[0010]
Technical Solution
[0011] As shown in Patent Document 1 and Patent Document 2, in order to suppress the expansion and contraction of the battery during charging and discharging, it has been considered to include a soft adhesive crystal in the negative electrode or the solid electrolyte of the full solid rechargeable battery, but the effect is not sufficient.
[0012] Accordingly, as a result of repeated examinations by the inventors, it has been found that the above-mentioned problems can be solved by causing the positive electrode to include a predetermined ionically soft adhesive crystal, and the present invention has been completed for the first time.
[0013] That is, the positive electrode for a full-solid rechargeable battery and the full-solid rechargeable battery according to the present application are as follows.
[0014] The embodiments provide a positive electrode for a full-solid rechargeable battery, including a positive electrode current collector and a positive electrode mixture layer stacked on the positive electrode current collector, wherein the positive electrode mixture layer includes a positive electrode active material capable of intercalating and deintercalating lithium ions, a sulfide solid electrolyte, and an ionically soft sticky crystal including a cyclic disulfimide-based anion (e.g., 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide (CFSI)) anion.
[0015] The ionically sticky crystal can include an ammonium-based cation, a pyrrolidinium-based cation, a pyridinium-based cation, a pyrimidinium-based cation, an imidazolium-based cation, a piperidinium-based cation, a pyrazolium-based cation, an oxazolinium-based cation, a pyridazinium-based cation, a phosphonium-based cation, a sulfonium-based cation, a triazolium-based cation, or a combination thereof as the cation.
[0016] The cation can be a cation selected from a spiro-ammonium, a pyrrolidinium, a piperidinium, a tetraalkylammonium, or a combination thereof.
[0017] The cyclic disulfimide-based anion can be represented by Chemical Formula 1.
[0018] [Chemical Formula 1]
[0019]
[0020] In Chemical Formula 1, R is hydrogen, a fluorine group, or a C1-C10 fluorine alkyl group, n is an integer of 1-6, and at least one of the plurality of R is a fluorine group or a C1-C10 fluorine alkyl group.
[0021] The cyclic disulfimide-based anion can include a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion.
[0022] The amount of the ionically soft sticky crystal in the positive electrode mixture layer can be greater than or equal to 0.05 wt% and less than or equal to 20 wt% based on 100 wt% of the positive electrode mixture layer.
[0023] The amount of the ionically soft sticky crystal in the positive electrode mixture layer can be greater than or equal to 0.1 wt% and less than or equal to 15 wt% based on 100 wt% of the positive electrode mixture layer.
[0024] The positive electrode mixture layer can additionally include a conductive aid and a binder.
[0025] The all-solid-state rechargeable battery includes a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, wherein the positive electrode can be the positive electrode for an all-solid-state rechargeable battery as described in any one of the foregoing embodiments.
[0026]
[0027] According to the positive electrode for an all-solid-state rechargeable battery or the all-solid-state rechargeable battery configured in this way, because the positive electrode mixture layer includes an ionically viscous crystal including a cyclic disulfimide-based anion (e.g., a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide (CFSI) anion), even when a volume change of the battery occurs due to lithium intercalation, extraction, or dissolution during charging and discharging, damage to the battery in the positive electrode, the negative electrode, the solid electrolyte layer, and their interfaces can be suppressed. As a result, even in the case of an all-solid-state rechargeable battery in which a volume change occurs as described above, even when no external pressure is applied or when a low external pressure is applied, degradation of battery performance can be sufficiently suppressed. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 A cross-sectional schematic view to show a structure of an all-solid-state rechargeable battery according to an embodiment of the present application.
[0029] Figure 2 A cross-sectional schematic view to show a structure of a positive electrode of an all-solid-state rechargeable battery according to an embodiment.
[0030] Figure 3a and Figure 3b A graph to compare battery performance of Embodiment 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0031] Hereinafter, specific embodiments are described in detail with reference to the accompanying drawings so that those having ordinary knowledge in the technical field to which the disclosure pertains can easily practice them. However, the disclosure can be embodied in many different forms and is not explained as limited to the example embodiments set forth herein.
[0032] On the other hand, in the present specification and drawings, components having substantially the same function are designated by the same reference numerals, and redundant descriptions are omitted.
[0033] The terminology used herein is for the purpose of describing embodiments only and is not intended to limit the present application. Singular expressions include plural expressions unless the context clearly dictates otherwise.
[0034] As used herein, "combinations thereof' means mixtures, laminates, composites, copolymers, alloys, blends, reaction products, or the like of the constituents.
[0035] Here, it is to be understood that the terms such as "comprises", "includes", or "has", are intended to denote the existence of the stated features, numbers, steps, elements, or combinations thereof, but do not preclude the presence or addition of one or more other features, numbers, steps, elements, or combinations thereof.
[0036] It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements can also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0037] In addition, a "layer" in this document includes not only a shape formed on an entire surface when viewed from a plan view, but also a shape formed on a partial surface.
[0038] <1, Basic configuration of all-solid-state rechargeable battery according to the present embodiment>
[0039] As shown in FIG. 1, an all-solid-state rechargeable battery 1 according to the present embodiment includes a positive electrode 10, a negative electrode 20, a solid electrolyte layer 30, and a case 40 in which they are accommodated. Figure 1
[0040] (1-1, Positive electrode)
[0041] The positive electrode 10 includes a positive electrode current collector 11 and a positive electrode mixture layer 12. Examples of the positive electrode current collector 11 can include a plate-like body or a thin body made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 can be omitted.
[0042] The positive electrode mixture layer 12 can include a positive electrode active material and a solid electrolyte. Also, the solid electrolyte included in the positive electrode is a sulfide solid electrolyte of the same type or a different type from the sulfide solid electrolyte described in the claims of the solid electrolyte layer 30.
[0043] The positive electrode active material can be any positive electrode active material capable of reversibly intercalating and deintercalating lithium ions.
[0044] For example, the positive electrode active material can include lithium salts such as cobalt lithium oxide (hereinafter referred to as "LCO"), lithium nickel oxide, lithium nickel cobalt oxide, and nickel cobalt aluminum lithium (hereinafter referred to as "NCA"), nickel cobalt manganese lithium (hereinafter referred to as "NCM"), lithium manganese oxide, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, sulfur, iron oxide, vanadium oxide, and the like. These positive electrode active materials can be used individually, and can be used in combination of two or more.
[0045] In addition, the positive electrode active material is preferably formed of a lithium salt including a transition metal oxide having a layered rock salt structure among the aforementioned lithium salts. Here, the "layered rock salt structure" is a structure in which oxygen atom layers and metal atom layers are alternately arranged in the <111> direction of a cubic rock salt structure and as a result each atom layer forms a two-dimensional plane. In addition, the "cubic rock salt structure" refers to a sodium chloride type structure, which is a type of crystal structure, and specifically refers to a structure in which face-centered cubic lattices formed by each of cations and anions are arranged offset from each other by only 1 / 2 of a unit lattice corner.
[0046] Examples of the lithium salt of the transition metal oxide having such a layered rock salt structure can include lithium salts of ternary transition metal oxides such as LiNi x Co y Al z O2(NCA) or LiNi x Co y Mn z O2(NCM) (0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1).
[0047] When the positive electrode active material includes a lithium salt of a ternary transition metal oxide having the aforementioned layered rock salt structure, the energy density and thermal stability of the all-solid-state rechargeable battery 1 can be improved.
[0048] The positive electrode active material can be covered with a coating layer. Here, the coating layer of the present embodiment can be any coating layer as long as it is a well-known coating layer of the positive electrode active material of the all-solid-state rechargeable battery. Examples of the coating layer can include Li2O-ZrO2and the like.
[0049] In addition, when the positive electrode active material is formed of a lithium salt of a ternary transition metal oxide such as NCA or NCM and includes nickel (Ni) as the positive electrode active material, the capacity density of the all-solid-state rechargeable battery 1 increases, and metal elution from the positive electrode active material in the charged state can be reduced. Accordingly, the all-solid-state rechargeable battery 1 according to the present embodiment can improve long-term reliability and cycle characteristics in the charged state.
[0050] In this context, the positive electrode active material can have a shape of a particle, such as a regular spherical shape and an ellipsoidal shape. In addition, the particle diameter of the positive electrode active material is not particularly limited, and can be within a range suitable for a positive electrode active material of a conventional full solid-state rechargeable battery. Meanwhile, the amount of the positive electrode active material in the positive electrode 10 is also not particularly limited, as long as it is within a range suitable for the positive electrode 10 of the conventional full solid-state rechargeable battery.
[0051] Further, in the positive electrode 10, in addition to the aforementioned positive electrode active material and solid electrolyte, for example, an additive such as a conductive aid, a binder, a filler, a dispersant, or an ion conductive aid can be appropriately admixed.
[0052] Examples of the conductive aid that can be admixed in the positive electrode 10 can include graphite, carbon black, acetylene black, ketjen black, carbon fiber, and metal powder. In addition, the binder that can be admixed in the positive electrode 10 can include, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, or the like. In addition, as the filler, dispersant, ion conductive aid, or the like that can be admixed in the positive electrode 10, a well-known material that can be generally used for an electrode of a full solid-state rechargeable battery can be used.
[0053] (1-2, Negative Electrode)
[0054] The negative electrode 20 can include a negative electrode current collector 21 and a negative electrode mixture layer 22 on the negative electrode current collector 21. The negative electrode current collector 21 can desirably be made of a material that does not react with lithium (i.e., neither forms an alloy nor forms a compound). Examples of the material that constitutes the negative electrode current collector 21 can include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni).
[0055] The negative electrode mixture layer 22 includes a negative electrode active material, a carbon material, and a binder.
[0056] The negative electrode active material can be, for example, an alloy-forming element, which is an element that forms an alloy or a compound with lithium through an electrochemical reaction during charging.
[0057] The alloy-forming element can be any one or more types selected from gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, and zinc.
[0058] When one or more of gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, and zinc is used as the alloy-forming element, it is desirable that these negative electrode active materials be in the form of a particle, for example, and the particle size is less than or equal to 4 μm, and more desirably less than or equal to 300 nm. In this case, the characteristics of the full solid-state rechargeable battery 1 are further improved. In this context, the particle size of the negative electrode active material can be, for example, a median diameter (so-called D 50 ).
[0059] Examples of the carbon material include amorphous carbon such as carbon black and graphene. Examples of the carbon black can include acetylene black, furnace black, and ketjen black.
[0060] In addition to those described above, the negative electrode mixture layer 22 can also include appropriate additives (such as a filler, a dispersant, an ion conductive agent, and a solid electrolyte) used in a conventional all-solid rechargeable battery.
[0061] (1-3, Solid electrolyte layer)
[0062] The solid electrolyte layer 30 is formed between the positive electrode 10 and the negative electrode 20 and includes a solid electrolyte.
[0063] The solid electrolyte is, for example, in a powder form and is composed of, for example, a sulfide-based solid electrolyte material.
[0064] The sulfide-based solid electrolyte material can be, for example, Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element, for example, I, Br, or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, and Z is any one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers and M is any one of P, Si, Ge, B, Al, Ga, or In). Here, the sulfide-based solid electrolyte material is prepared by processing starting materials (for example, Li2S, P2S5, and the like) using a melt quenching method or a mechanical grinding method. In addition, further heat treatment can be performed after these processes. The solid electrolyte can be amorphous, crystalline, or a mixture thereof.
[0065] In addition, as the solid electrolyte, among the above-mentioned sulfide-based solid electrolyte materials, it is desirable to use a material including at least one element selected from sulfur, silicon, phosphorus, and boron. Accordingly, the lithium conductivity of the solid electrolyte layer 30 is improved, and the battery characteristics of the all-solid rechargeable battery 1 are improved. In particular, it is preferable to use a solid electrolyte including at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements, and it is more desirable to use a solid electrolyte including Li2S-P2S5.
[0066] Here, when a sulfide-based solid electrolyte material including Li2S-P2S5 is used to form the solid electrolyte, the mixed molar ratio of Li2S and P2S5 can be selected within a range of, for example, Li2S:P2S5 = 50:50 to 90:10.
[0067] The solid electrolyte layer 30 can further include a binder, and examples of the binder include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, and the like. The binder in the solid electrolyte layer 30 can be the same as or different from the binder in the positive electrode mixture layer 12 and the negative electrode mixture layer 22.
[0068] (1-4, Relationship between charge capacity of positive electrode and negative electrode)
[0069] The all-solid-state rechargeable battery 1 according to the present embodiment is configured so that the ratio (i.e., the capacity ratio) of the charge capacity of the positive electrode mixture layer 12 to the charge capacity of the negative electrode mixture layer 22 satisfies the condition of Equation 1.
[0070] [Equation 1]
[0071] 0.01 < b / a < 0.5 (1)
[0072] In Equation 1,
[0073] a is the charge capacity (mAh) of the positive electrode mixture layer 12, and b is the charge capacity (mAh) of the negative electrode mixture layer 22.
[0074] Here, the charge capacity of the positive electrode mixture layer 12 is obtained by multiplying the charge capacity density (mAh / g) of the positive electrode active material by the weight of the positive electrode active material in the positive electrode mixture layer 12. When multiple types of positive electrode active materials are used, the value of the charge capacity density x weight is calculated for each positive electrode active material, and the sum of these values is used as the charge capacity of the positive electrode mixture layer 12. The charge capacity of the negative electrode mixture layer 22 is also calculated in the same manner. That is, the charge capacity of the negative electrode mixture layer 22 is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the weight of the negative electrode active material in the negative electrode mixture layer 22. When multiple types of negative electrode active materials are used, the value of the charge capacity density x weight is calculated for each negative electrode active material, and the sum of these values is used as the capacity of the negative electrode mixture layer 22. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is the evaluation capacity of the all-solid-state half battery using lithium metal as the counter electrode. In practice, the charge capacity of the positive electrode mixture layer 12 and the negative electrode mixture layer 22 is directly measured by measurement using the all-solid-state half battery.
[0075] As a specific method for directly measuring the charge capacity, the following method can be described as an example. First, the charge capacity of the positive electrode mixture layer 12 is measured by manufacturing a test battery cell using the positive electrode mixture layer 12 as a working electrode and Li as a counter electrode and performing CC-CV charging from OCV (open circuit voltage) to an upper limit charging voltage. The upper limit charging voltage is determined by the standard of JIS C 8712:2015, and for a lithium cobaltate type positive electrode, the upper limit charging voltage refers to the voltage obtained by applying the provision of JIS C 8712:2015 A.3.2.3 (safety requirements when applying different upper limit charging voltages), and for other types of positive electrodes, the upper limit charging voltage is 4.25 V. As for the charge capacity of the negative electrode mixture layer 22, a test battery cell is manufactured using the negative electrode mixture layer 22 as a working electrode and Li as a counter electrode, and the charge capacity is measured by performing CC-CV charging from OCV (open circuit voltage) to 0.01 V.
[0076] For the battery cell of the above-described test, it can be manufactured, for example, in the following manner. The positive electrode mixture layer 12 or the negative electrode mixture layer 22, the charge capacity of which is to be measured, is punched into a circular shape having a diameter of 13 mm. 200 mg of the same solid electrolyte powder used in the all-solid-state rechargeable battery 1 is solidified at 40 MPa and made into a pellet shape having a diameter of 13 mm and a thickness of approximately 1 mm. The pellet is placed inside a can having an inner diameter of 13 mm, the positive electrode mixture layer 12 or the negative electrode mixture layer 22 having a circular plate shape is placed from one side, and a lithium foil having a diameter of 13 mm and a thickness of 0.03 mm is placed from the opposite side. In addition, one stainless steel tab is inserted from each side, and the entire body is pressurized in the axial direction at 300 MPa for 1 minute to integrate the contents. The integrated contents are taken out of the container and sealed in a case so that a pressure of 22 MPa is always applied to prepare a test battery cell. The charge capacity of the positive electrode mixture layer 12 can be measured by, for example, charging the test battery cell manufactured as described above with CC at a current density of 0.1 mA and then charging with CV up to 0.02 mA.
[0077] The charge capacity density is calculated by dividing this charge capacity by the weight of each active material. The initial charge capacity of the positive electrode mixture layer 12 and the negative electrode mixture layer 22 can be the initial charge capacity measured during the first charge cycle. In the example described below, this value is used.
[0078] Thus, the charge capacity of the positive electrode mixture layer 12 becomes excessive relative to the charge capacity of the negative electrode mixture layer 22. As described below, in this embodiment, the all-solid-state rechargeable battery 1 is charged beyond the charge capacity of the negative electrode mixture layer 22. That is, the negative electrode mixture layer 22 is overcharged. At the start of charging, lithium is intercalated into the negative electrode mixture layer 22. That is, the negative electrode active material forms an alloy with lithium ions that move from the positive electrode 10. When further charging is performed beyond the capacity of the negative electrode mixture layer 22, as shown in FIG. 2, lithium is deposited on the back surface of the negative electrode mixture layer 22, that is, between the negative electrode current collector 21 and the negative electrode mixture layer 22, and a lithium deposition layer 23 is formed from this lithium. The lithium deposition layer 23 is mainly composed of lithium (mainly metallic lithium), but the lithium deposition layer 23 also contains trace amounts of elements other than lithium. Figure 2 As shown in FIG. 2, lithium is deposited on the back surface of the negative electrode mixture layer 22, that is, between the negative electrode current collector 21 and the negative electrode mixture layer 22, and a lithium deposition layer 23 is formed from this lithium. The lithium deposition layer 23 is mainly composed of lithium (mainly metallic lithium), but the lithium deposition layer 23 also contains trace amounts of elements other than lithium.
[0079] This phenomenon is caused by containing a specific substance as the negative electrode active material, that is, an alloy-forming element that forms an alloy or a compound with lithium. During discharging, lithium in the negative electrode mixture layer 22 and the lithium deposition layer 23 is ionized and moves toward the positive electrode 10. Therefore, in the all-solid-state rechargeable battery 1 according to this embodiment, the deposited lithium can be used as a negative electrode active material. In addition, because the negative electrode mixture layer 22 covers the lithium deposition layer 23, the negative electrode mixture layer 22 functions as a protective layer for the lithium deposition layer 23 and can suppress the deposition and growth of dendrites. Accordingly, short-circuiting and capacity reduction of the all-solid-state rechargeable battery 1 are suppressed, and further, the characteristics of the all-solid-state rechargeable battery 1 are improved.
[0080] Here, the capacity ratio is greater than 0.01. When the capacity ratio is less than 0.01, the characteristics of the all-solid-state rechargeable battery 1 can be degraded. As a reason therefor, one example can be that the negative electrode mixture layer 22 cannot sufficiently function as a protective layer. For example, when the thickness of the negative electrode mixture layer 22 is very thin, the capacity ratio can be less than or equal to 0.01. In this case, there is a possibility that the negative electrode mixture layer 22 can collapse due to repeated charging and discharging, cause deposition and growth of dendrites. As a result, the characteristics of the all-solid-state rechargeable battery 1 are degraded. In Patent Document 1, it is presumed that the interface layer or the carbon layer is too thin, and thus the characteristics of the all-solid-state rechargeable battery are not sufficiently improved. In addition, it is desirable that the capacity ratio be less than 0.5. This is because when the capacity ratio above is greater than or equal to 0.5, it is believed that the amount of lithium deposited in the negative electrode decreases, and the battery capacity decreases. For the same reason, it is more desirable that the capacity ratio be less than 0.25. In addition, by having a capacity ratio less than 0.25, the output characteristics of the battery can be further improved.
[0081] The thickness of the negative electrode mixture layer 22 is not particularly limited as long as it satisfies the requirement of Equation 1, but it is desirable to be greater than or equal to 1 μm and less than or equal to 20 μm, more desirably greater than or equal to 1 μm and less than or equal to 10 μm. If the thickness of the negative electrode mixture layer 22 is less than 1 μm, there is a possibility that the characteristics of the all-solid-state rechargeable battery 1 will not be sufficiently improved. If the thickness of the negative electrode mixture layer 22 exceeds 20 μm, the electrical resistance of the negative electrode mixture layer 22 increases, and as a result, there is a possibility that the characteristics of the all-solid-state rechargeable battery 1 will not be sufficiently improved.
[0082] The thickness of the aforementioned negative electrode mixture layer 22 can be evaluated, for example, by observing the average thickness of a cross section using a scanning electron microscope (SEM) after the all-solid-state rechargeable battery 1 is assembled and molded.
[0083] <2, Characteristic Configuration of the All-Solid-State Rechargeable Battery Cell According to the Present Embodiment>
[0084] In the present embodiment, the positive electrode 10 further includes an ionically soft sticky crystal in addition to the aforementioned components. Specifically, an example can be one in which the positive electrode mixture layer includes an ionically soft sticky crystal.
[0085] A soft sticky crystal is an intermediate state between a solid crystal and a liquid, and refers to a state in which the three-dimensional positions of the constituent particles are regular, but the orientation of the particles is irregular.
[0086] The soft sticky crystal in the present embodiment is ionic, and contains a cation and an anion.
[0087] The cation can be, for example, one or more cations selected from the group consisting of ammonium-based cations, pyrrolidinium-based cations, pyridinium-based cations, pyrimidinium-based cations, imidazolium-based cations, piperidinium-based cations, pyrazolium-based cations, oxazolinium-based cations, pyridazinium-based cations, phosphonium-based cations, sulfonium-based cations, triazolium-based cations, and mixtures thereof.
[0088] Among these, it is desirable to use a screw-type ammonium-based, tetraalkylammonium-based, pyrrolidinium-based, and pyridinium-based cation. Here, the alkyl group can be an alkyl group having 1 to 20 carbon atoms, for example, an alkyl group having 1 to 10 carbon atoms.
[0089] Specific examples can include 5-azaspiro[4,4]nonane (SBP), N-ethyl-N-methylpyrrolidinium (P12), tetramethylammonium (TMA), N,N-dimethylpiperidinium (P11), triethylmethylammonium (TEMA), tetrapropylammonium (TPA), and ethyltrimethylammonium (ETMA).
[0090] In the present embodiment, the anion includes a cyclic disulfimide anion. The cyclic disulfimide anion can be represented by Chemical Formula 1.
[0091] [Chemical Formula 1]
[0092]
[0093] In Chemical Formula 1, R is hydrogen, a fluoro group, or a C1-C10 fluoroalkyl group, n is an integer of 1 to 6, and at least one of the plurality of R is a fluoro group or a C1-C10 fluoroalkyl group.
[0094] For example, the cyclic disulfimide anion can be a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion (hereinafter also referred to as CFSI).
[0095] As described above, the ionic soft sticky crystal contains a cation and an anion, and for example, when it contains 5-azaspiro[4,4]nonane as the cation and a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion as the anion, it can be expressed as 5-azaspiro[4,4]nonane 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion. For the ionic soft sticky crystal according to the present embodiment, because there are a variety of candidate substances for the cation as described above, various types of ionic soft sticky crystals can be used by replacing the cation with a different type and changing the combination of the cation and the anion.
[0096] The amount of the ionic soft sticky crystal in the positive electrode mixture layer 12 (when the total positive electrode mixture layer 12 is 100 wt%) is desirably greater than or equal to 0.05 wt% and less than or equal to 20 wt%, more desirably greater than or equal to 0.1 wt% and less than or equal to 15 wt%, and even more desirably greater than or equal to 0.5 wt% and less than or equal to 10 wt%.
[0097] The ionic sticky crystal can further contain a lithium salt.
[0098] Any of the lithium salts used as the lithium salt in the technical field above can be used. The lithium salt is, for example, one of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, Li(FSO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(CxF2x+1SO2)(CyF2y+1SO2) (where x and y are natural numbers), LiCl, LiI, or a mixture thereof. s F6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, Li(FSO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+ 1SO2)(C y F 2y+1 SO2) (where x and y are natural numbers), LiCl, LiI, or a mixture thereof.
[0099] The concentration of the lithium salt included in the ionic viscous crystal is desirably 0.1 M to 5 M.
[0100] <3> Method of manufacturing the all-solid rechargeable battery according to the present embodiment
[0101] Next, a method for manufacturing the all-solid rechargeable battery 1 according to the present embodiment will be described. The all-solid rechargeable battery 1 according to the present embodiment can be manufactured by manufacturing the positive electrode 10, the negative electrode 20, and the solid electrolyte layer 30 respectively and then stacking each of the above layers.
[0102] (3-1, Manufacturing process of positive electrode)
[0103] First, materials constituting the positive electrode mixture layer 12 (positive electrode active material, solid electrolyte, binder, etc.) are mixed and processed into a thin sheet shape, and the thin sheet is impregnated with an ionic soft viscous crystal to form a positive electrode mixture thin sheet.
[0104] The positive electrode mixture thin sheet obtained in this way is cut into an appropriate shape and stacked on the positive electrode current collector as a positive electrode mixture layer material, and the obtained stack is pressed (for example, by using hydrostatic pressure pressing), thereby manufacturing the positive electrode 10 including the positive electrode current collector and the positive electrode mixture layer.
[0105] (3-2, Manufacturing process of negative electrode)
[0106] First, a slurry is prepared by adding a negative electrode mixture layer material constituting the negative electrode mixture layer 22 (negative electrode active material, non-alloying element, binder, etc.) to a polar solvent or a non-polar solvent. Subsequently, the obtained slurry is coated on the negative electrode current collector 21 and dried. Next, the obtained stack is pressed (for example, by using hydrostatic pressure pressing) to produce the negative electrode 20. The pressing process can be omitted. Meanwhile, the negative electrode 20 can be manufactured by separately forming the negative electrode mixture layer 22 and then stacking it on the negative electrode current collector 21 and pressing.
[0107] (3-3, Manufacturing process of solid electrolyte layer)
[0108] The solid electrolyte layer 30 can be manufactured, for example, by the following sequence or process.
[0109] First, the starting material is treated by a melt-quenching method or a mechanical grinding method.
[0110] For example, when the melt-quenching method is used, a sulfide-based solid electrolyte material is prepared by mixing starting materials (e.g., Li2S, P2S5, etc.) in respective predetermined amounts and granulating, and then reacting and quenching under vacuum at a predetermined reaction temperature. Meanwhile, the reaction temperature of the Li2S and P2S5 mixture can desirably be 400 °C to 1000 °C and more desirably 800 °C to 900 °C. In addition, the reaction time can desirably be about 0.1 hour to about 12 hours and more desirably about 1 hour to about 12 hours. Furthermore, the quenching temperature of the reactants can generally be less than or equal to 10 °C and desirably less than or equal to 0 °C, and the quenching rate can generally be 1 °C / sec to 10000 °C / sec and desirably 1 °C / sec to 1000 °C / sec.
[0111] In addition, when the mechanical milling method is used, a sulfide-based solid electrolyte material is prepared by stirring and reacting starting materials (e.g., Li2S, P2S5, etc.) using a ball mill or the like. Meanwhile, the mechanical milling method is not particularly limited with respect to the stirring speed and stirring time, but as the stirring speed is faster, the sulfide-based solid electrolyte material can be produced faster, and as the stirring is made for a longer time, the conversion rate of the starting materials to the sulfide-based solid electrolyte material can increase.
[0112] Thereafter, the mixed raw material obtained in the melt-quenching method or the mechanical milling method is heat-treated at a predetermined temperature and pulverized, to prepare a solid electrolyte in a granular form. When the solid electrolyte has a glass transition point, it can be changed from amorphous to crystalline by heat treatment.
[0113] Subsequently, the solid electrolyte obtained in the aforementioned method can be formed into a solid electrolyte layer 30 in a known film-forming method (e.g., an aerosol deposition method, a cold spray method, a sputtering method, etc.). Meanwhile, the solid electrolyte layer 30 can be produced by pressing a solid electrolyte granular group. In addition, the solid electrolyte layer 30 can be formed by mixing a solid electrolyte, a solvent, and a binder, and then coating and drying the mixture.
[0114] (3-4, Assembly process of all-solid-state rechargeable battery)
[0115] The all-solid-state rechargeable battery 1 according to the present embodiment can be manufactured by stacking the positive electrode 10, the negative electrode 20, and the solid electrolyte layer 30 manufactured by the above-described method such that the solid electrolyte layer 30 is interposed between the positive electrode 10 and the negative electrode 20 and applying pressure (e.g., applying pressure using hydrostatic pressure).
[0116] <4, Charging method of all-solid-state rechargeable battery according to the present embodiment>
[0117] Next, a charging method of the all-solid-state rechargeable battery 1 is described. In this embodiment, as described above, the all-solid-state rechargeable battery 1 is charged over the charge capacity of the negative electrode mixture layer 22. That is, the negative electrode mixture layer 22 is overcharged. At the start of charging, lithium is intercalated into the negative electrode mixture layer 22. When charging over the charge capacity of the negative electrode mixture layer 22 is performed, for example, as described above, lithium is deposited on the back surface of the negative electrode mixture layer 22, that is, between the negative electrode current collector 21 and the negative electrode mixture layer 22, and a lithium deposition layer 23 that was not present during manufacture is formed from this lithium. During discharge, the lithium in the negative electrode mixture layer 22 and the lithium deposition layer 23 is ionized and moves toward the positive electrode 10. Figure 1 As shown in FIG. 6, lithium is deposited on the back surface of the negative electrode mixture layer 22, that is, between the negative electrode current collector 21 and the negative electrode mixture layer 22, and a lithium deposition layer 23 that was not present during manufacture is formed from this lithium. During discharge, the lithium in the negative electrode mixture layer 22 and the lithium deposition layer 23 is ionized and moves toward the positive electrode 10.
[0118] Also, the desired amount of charge is a value between 2 times and 100 times the charge capacity of the negative electrode mixture layer 22, more desirably between 4 times and 100 times.
[0119] The thickness of the lithium deposition layer 23 deposited in the negative electrode during charging is desirably greater than or equal to 10 μm, more desirably greater than or equal to 30 μm, and desirably within a range of less than or equal to 60 μm, which is the upper limit of usability as an all-solid-state rechargeable battery. Meanwhile, the thickness of this lithium deposition layer 23 can be measured by observing the average thickness of the cross section using a scanning electron microscope (SEM) after charging the all-solid-state rechargeable battery 1.
[0120] <5,Effects of the Embodiment>
[0121] According to the positive electrode for an all-solid-state rechargeable battery or the all-solid-state rechargeable battery according to the embodiment, the positive electrode mixture layer contains an ionically soft viscous crystal having a cyclic disulfimide anion (for example, a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion, hereinafter referred to as CFSI) as an anion, and even when the battery has a large volume change such as when lithium is deposited due to overcharging over the negative electrode capacity as described above, because the deterioration of the battery performance can be sufficiently suppressed, the battery can be charged and discharged without problems by not applying an external pressure or applying an external pressure that is sufficiently low.
[0122] <6,Another Embodiment of the Invention>
[0123] As mentioned above, although the present invention is described in detail with respect to the embodiments with reference to the attached drawings, the present disclosure is not limited thereto. Various examples that can be changed or modified within the scope of the technical idea described in the claims can be understood by those of ordinary skill in the art to which the present invention pertains, and thus these can also be within the technical scope of the present invention.
[0124]
Way of Invention
[0125] Embodiments
[0126] Examples of an all-solid rechargeable battery according to the present disclosure will be described in more detail below, but the present disclosure is not limited thereto.
[0127] Examples 1 to 12 and Comparative Examples 1 and 2
[0128] <Preparation of ionically soft adhesive crystal>
[0129] An ionically soft adhesive crystal (5-azaspiro[4.4]nonane 1.1.2.2.3.3-hexafluoropropane-1.3-disulfonimide (SBPCFSI)) was synthesized as follows.
[0130] 10 g of 5-azaspiro[4.4]nonane chloride (SBPCl) was dissolved in 100 mL of ultrapure water. Subsequently, after 18.5 g of 1.1.2.2.3.3-hexafluoropropane-1.3-disulfonimide lithium (LiCFSI) was dissolved in 100 mL of ultrapure water, the SBPCl aqueous solution was added dropwise to the solution. The obtained white solid was recovered by filtration, rinsed with distilled water or the like, and vacuum-dried at 120 °C for 12 hours to obtain the target ionically soft adhesive crystal.
[0131] Other ionically soft adhesive crystals were synthesized in the same order as above.
[0132] <Manufacture of positive electrode>
[0133] LiNi 0.8 Co 0.15 Mn 0.05 O2 (NCM) as a positive electrode active material, Li6PS5Cl as a solid electrolyte, carbon nanotube (CNT) as a conductive agent, and Teflon (tetrafluoroethylene) binder as a binder were mixed in a weight ratio of 90:9.6:0.15:0.25 (= positive electrode active material: solid electrolyte: CNT: Teflon (tetrafluoroethylene) binder), and then molded into a thin sheet shape having about 2 cm x 2 cm to be used as a positive electrode mixture.
[0134] Subsequently, the ionic soft adhesive crystal SBPCFSI was dissolved in dichloromethane at a concentration of 2 wt%. The molded positive electrode sheet was immersed in the solution and impregnated therein by vacuum suction to -0.05 MPa. The positive electrode sheet was taken out of the solution and then dried to obtain a positive electrode sheet impregnated with the ionic soft adhesive crystal. The positive electrode mixtures of Examples 1 to 12 and Comparative Examples 1 and 2 were prepared to include each content of the ionic soft adhesive crystal as shown in Table 1 or Table 2 after drying, and then, pressed on an 18 μm thick aluminum film as a positive electrode current collector, to manufacture a positive electrode. On the other hand, the content of the ionic soft adhesive crystal in the positive electrode mixture was controlled by adjusting the concentration of the ionic soft adhesive crystal in the solution in which the positive electrode sheet was immersed, specifically, it is known that the concentration of the ionic soft adhesive crystal in the solution can be set to twice the target content. For example, when the positive electrode sheet is immersed in a solution containing 2 wt% of the ionic soft adhesive crystal, the finally obtained positive electrode mixture can contain about 1 wt% of the ionic soft adhesive crystal.
[0135] <Manufacture of all-solid-state rechargeable battery cell>
[0136] A slurry was prepared by placing 12 g of carbon black and 4 g of silver particles in a container and then stirring while gradually adding thereto an NMP solution including 8 wt% of a binder (Kureha Corp.) to the container, wherein the amount of the binder was set to 7 wt% of the solid content. The slurry was coated on a 10 μm thick stainless steel film with a doctor blade coater, and then dried in air at 80 °C for about 20 minutes and vacuum dried at 100 °C for about 12 hours, to manufacture a negative electrode.
[0137] Subsequently, a solid electrolyte sheet was manufactured in the following method. A binder was added to a Li6PS5Cl solid electrolyte at 1 wt%, and then stirred while adding thereto xylene and isobutyl isobutyrate, to prepare a slurry. The slurry was coated on a PET film with a doctor blade coater, and then dried in air at 40 °C and vacuum dried at 40 °C for 12 hours.
[0138] The solid electrolyte sheet manufactured in this way was overlapped so that the solid electrolyte surface and the negative electrode surface were combined, and then, isostatically pressed at 50 MPa and transferred on the negative electrode by peeling the PET film. Subsequently, a positive electrode was stacked on the obtained negative electrode / solid electrolyte integrated sheet, and then vacuum sealed in a lamination film. Each part of the positive electrode and the negative electrode was designed to protrude from the lamination film so as not to break the vacuum of the battery cell, and used as a positive electrode terminal and a negative electrode terminal, respectively.
[0139] Finally, isotropic pressurization at 490 MPa was performed to improve the battery characteristics, and a full-solid-state rechargeable battery cell was obtained.
[0140] <Assessment of the full-solid-state rechargeable battery cell>
[0141] The full-solid-state lithium battery cell manufactured as described above was assessed for charge and discharge characteristics under a constraint pressure of 0.3 MPa or 0 MPa under the following conditions.
[0142] The measurement was performed by placing the full-solid-state lithium battery cell in a constant-temperature bath at 45 °C. The full-solid-state battery cell was inserted between two rigid stainless steel plates, and the stainless steel plates were fastened at the four corners with screws to apply a predetermined pressure thereto.
[0143] The battery cell was charged at a constant current of 4.6 mA / cm 2 to a battery voltage of 4.25 V and charged at a constant voltage of 4.25 V to a current of 1.4 mA / cm 2 . Then, the battery cell was discharged at a constant current of 4.6 mA / cm 2 to a battery voltage of 2.5 V. This charge / discharge was repeated 50 times to measure the capacity retention (cycle life) and average coulombic efficiency (1 C discharge characteristics), which are shown in Tables 1 and 2. The average coulombic efficiency in Table 2 is expressed as a relative value based on 100% of Comparative Example 1. In addition, Figure 3a and Figure 3b are graphs showing the average coulombic efficiency (1 C discharge characteristics) and the capacity retention of Example 1 and Comparative Example 1, respectively.
[0144] (Table 1)
[0145]
[0146] (Table 2)
[0147]
[0148] In Tables 1 and 2, SBP is 5-azaspiro[4,4]nonane, P11 is N,N-dimethylpiperidinium, P12 is N-ethyl-N-methylpyrrolidinium, TEMA is triethylmethylammonium, TPA is tetrapropylammonium, TMA is tetramethylammonium, ETMA is ethyltrimethylammonium, CFSI is 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonimide, and TFSI is bis(trifluoromethane)sulfonimide.
[0149] <Considerations>
[0150] Referring to the results of Table 1, when a positive electrode including an ionic soft sticky crystal containing CFSI as an anion is used, the capacity retention and 1 C discharge characteristics are found to be significantly improved compared to those of conventional ones with a sufficiently low restraint pressure such as 0.3 MPa.
[0151] It is understood that this result is obtained because the soft sticky crystal suppresses delamination of the interface between the solid electrolyte and the positive electrode active material due to expansion and shrinkage of the positive electrode active material during charging and discharging.
[0152] In addition, referring to the results of Table 2, even when no restraint pressure is applied, the battery characteristics are improved by about twice compared to those of conventional ones, which demonstrates the importance of the present application to realizing a full solid rechargeable battery that can be used without applying a restraint pressure.
[0153] In addition, it is confirmed that the ionic soft sticky crystal containing CFSI as an anion is important compared to Comparative Example 2.
[0154] While the present application has been described in connection with the embodiments presently conceived as practical, it is understood that the present application is not limited to the disclosed embodiments, but, rather, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0155] [Legend of Reference Numerals]
[0156] 1 full solid rechargeable battery
[0157] 10 positive electrode
[0158] 11 positive electrode current collector
[0159] 12 positive electrode mixture layer
[0160] 20 negative electrode
[0161] 21 negative electrode current collector
[0162] 22 negative electrode mixture layer
[0163] 23 lithium precipitation layer
[0164] 30 solid electrolyte layer
Claims
1. A positive electrode for an all-solid-state rechargeable battery, comprising: a positive electrode current collector, and a positive electrode mixture layer stacked on the positive electrode current collector, wherein the positive electrode mixture layer includes a positive electrode active material capable of intercalating and deintercalating lithium ions, a sulfide solid electrolyte, and an ionic soft sticky crystal including a cyclic disulfimide-based anion. 2.The positive electrode according to claim 1, wherein the ionic soft sticky crystal includes an ammonium-based cation, a pyrrolidinium-based cation, a pyridinium-based cation, a pyrimidinium-based cation, an imidazolium-based cation, a piperidinium-based cation, a pyrazolium-based cation, an oxazolinium-based cation, a pyridazinium-based cation, a phosphonium-based cation, a sulfonium-based cation, a triazolium-based cation, or a combination thereof as a cation. 3.The positive electrode according to claim 2, wherein the cation is selected from a spiro-type ammonium, a pyrrolidinium, a piperidinium, a tetraalkylammonium, or a combination thereof. 4.The positive electrode according to claim 1, wherein the cyclic disulfimide-based anion is represented by Chemical Formula 1: [Chemical Formula 1] wherein In Chemical Formula 1, R is hydrogen, a fluorine group, or a C1-C10 fluorinated alkyl group, n is an integer of 1-6, and at least one of the plurality of R is a fluorine group or a C1-C10 fluorinated alkyl group. 5.The positive electrode according to claim 1, wherein the cyclic disulfimide-based anion includes a 1,1,2,2,3,3-hexafluoropropane-1,3-disulfimide anion. 6.The positive electrode according to claim 1, wherein an amount of the ionic soft sticky crystal in the positive electrode mixture layer is greater than or equal to 0.05 wt% and less than or equal to 20 wt% based on 100 wt% of the positive electrode mixture layer. 7.The positive electrode according to claim 1, wherein an amount of the ionic soft sticky crystal in the positive electrode mixture layer is greater than or equal to 0.1 wt% and less than or equal to 15 wt% based on 100 wt% of the positive electrode mixture layer. 8.The positive electrode according to claim 1, wherein the positive electrode mixture layer further includes a conductive aid and a binder. 9.An all-solid-state rechargeable battery, comprising: a positive electrode; a negative electrode; and a solid electrolyte layer between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode for an all-solid-state rechargeable battery according to any one of claims 1-8. 10.The all-solid-state rechargeable battery according to claim 9, wherein the negative electrode includes at least one material selected from gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, and zinc, and amorphous carbon. 11.The all-solid-state rechargeable battery according to claim 9, wherein the negative electrode includes silver and amorphous carbon. 12.The all-solid-state rechargeable battery according to claim 9, wherein a ratio of an initial charge capacity of the positive electrode to an initial charge capacity of the negative electrode satisfies Equation 1: [Equation 1] 0.01 < b / a < 0.5 (1) In Equation 1, wherein a is the initial charge capacity (mAh) of the positive electrode, and b is the initial charge capacity (mAh) of the negative electrode.
13. A method for charging a full solid-state rechargeable battery, wherein the full solid-state rechargeable battery according to claim 9 is charged over the charge capacity of the negative electrode.
14. The method according to claim 13, wherein the charging is performed in a range of 2 times to 100 times the charge capacity of the negative electrode.
Citation Information
Patent Citations
Solid-state electrolyte layer for all-solid-state lithium-ion secondary battery and all-solid-state lithium-ion secondary battery including the same
JP2020198270A
Negative electrode for lithium ion battery
JP2021131979A